مخطوط تحلية الذهب في علم القضاء والأدب لأبي عمران موسى المازوني تحقيق ودراسة من الصفحة 140 الى الصفحة 149 - خليل, ياسين; عمار, شرين (My University, 2022)
"يصنف كتاب تحلية الذهب في علم القضاء والأدب، لأبي عمران موسى المازوني ضمن مؤلفات الفتاوى والنوازل وكتب النوازل، فبالإضافة إلى أنها كتب أحكامٍ فقهية، فهي بحق تصلح أن تكون أنموذجا للدارس و الباحث عن مناهج الفقهاء في الفتوى، والتعامل مع المستجدات، ويتوصل من خلالها إلى معرفة حالة الناس السياسية والاجتماعية ومناخهم وتضاريسهم، وأهم نشاطاتهم اليومية؛ لأن من خلال جواب الفقيه تعرف ملابسات القضية، وتفكير المجتمعات. الدراسة تتكون من قسمين: قسم دراسي يتضمن شخصية المؤلف، وتعريف الكتاب، وقسم تطبيقي فيه تحقيق لمسائله، ويجيب على هذه الإشكالية: هل هذا المخطوط صحيح النسبة لمؤلفه؟ وما هي الإضافة التي يقدمها تحقيق هذا المخطوط؟ "" The book of “gold desalination is classified in the science of justice and literature” by My Father Imran Musa Mazoni Among the writings of fatwas and houses and books of the comings in it, In addition to that it wrote jurisprudence, it can really be a model for the scholar and the researcher of the approaches of the jurists in the fatwa and dealing with developments and through which we can find out the political and social situation of the people their climate and topography and their most important daily activities because through the answer of the faqih you know the question and the circumstances of the case and coming down and the thinking of societies, the world has the right to be the destruction of a tribe. The purpose of this investigation is to solve the following problems:To what extent is the book reliable to the author? What is the desired addition of this study?"
مذكرة ماستر
Keywords: مخطوط - تحلية الذهب - علم القضاء والأدب- أبي عمران موسى المازوني - فقه.; Manuscript-gold desalination-judicial science and literature - Abu Imran Musa al - Mazouni-jurisprudence.